Multiple sessions of therapeutic electrical stimulation using implantable thin‐film wireless nerve stimulators improve functional recovery after sciatic nerve isograft repair - Birenbaum, Nathan K.; Yan, Ying; Odabas, Arman; Chandra, Nikhil S.; Ray, Wilson Z.; MacEwan, Matthew R. (Muscle & nerve, 2023)
Introduction/Aims Although therapeutic electrical stimulation (TES) of injured peripheral nerve promotes axon regeneration and functional recovery, clinical applications of this therapy are limited to the intraoperative timeframe. Implantable, thin‐film wireless nerve stimulators offer a potential solution to this problem by enabling delivery of electrical stimuli to an injured nerve over a period of several days post‐surgery. The aim of this study was to determine the optimal time course of stimulation for maximizing functional recovery in a rat sciatic nerve isograft repair model. Methods Adult male Lewis rats underwent thin‐film wireless nerve stimulator implantation following sciatic nerve transection and 40 mm nerve isograft repair. Immediately after surgery, animals began a daily regimen of TES for up to 12 consecutive days. Functional recovery was assessed by compound muscle action potential (CMAP), evoked muscle force, wet muscle mass, and axon counting. Results Serial CMAP measurements increased in amplitude over the course of the study, yet no significant difference between cohorts for serial or terminal CMAPs was observed. Axon counts and wet muscle mass measurements were greatest in the 6‐day stimulation group, which correlated with a significant increase in evoked muscle force for the 6‐day stimulation group at the terminal time point. Discussion Six daily sessions of TES were found to be most effective for augmenting functional recovery compared to other time courses of stimulation. Future studies should incorporate additional subjects and track axonal sprouting or measure neurotrophin levels during the therapeutic window to further elucidate the mechanisms behind, and ideal amount of, TES.